11+9x=2x-3

Simple and best practice solution for 11+9x=2x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11+9x=2x-3 equation:


Simplifying
11 + 9x = 2x + -3

Reorder the terms:
11 + 9x = -3 + 2x

Solving
11 + 9x = -3 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
11 + 9x + -2x = -3 + 2x + -2x

Combine like terms: 9x + -2x = 7x
11 + 7x = -3 + 2x + -2x

Combine like terms: 2x + -2x = 0
11 + 7x = -3 + 0
11 + 7x = -3

Add '-11' to each side of the equation.
11 + -11 + 7x = -3 + -11

Combine like terms: 11 + -11 = 0
0 + 7x = -3 + -11
7x = -3 + -11

Combine like terms: -3 + -11 = -14
7x = -14

Divide each side by '7'.
x = -2

Simplifying
x = -2

See similar equations:

| 47=4u-17 | | 27-2x=9 | | 7*6-12=5x+m | | 10s-40=-94 | | y(2y-5)=12 | | a*(t+z)=45*z+67 | | 6m+54=17 | | 9b-2= | | -c-4=1 | | g(r)=8r+4 | | 7+22=133 | | 4(-x+2)+3(x-1)=0 | | (2w+7x+5)(3w-5x)= | | x-3/5+2x=0 | | 5(x+1)=4(x-7) | | -5(3t-2)+2t=4t-3 | | 5(x+1)=(x-7) | | x(3x+2)+x(x+6)=7+x(4x+1) | | 12x+4=7x-30+4 | | 5+2(x+3)=10 | | 30x-4x=12-7x | | 7e^3x+2=27 | | 16x+y=80 | | X-(16/x)=6 | | 2x-(x-5)+3(x-1)=12 | | (6n^2-5n^3)+(n^3+5n^2)=0 | | -(2/3)*-5 | | √10/81 | | (6)(-3)+2(55-65)/-5= | | x(y^5+9)+9(y^5+9)= | | q(6-2q)=0 | | 50-30+80=-60 |

Equations solver categories